Points to consider for reporting, screening for and preventing selected comorbidities in chronic inflammatory rheumatic diseases in daily practice: a EULAR initiative. Issue 6 (16th March 2016) - Baillet, Athan; Gossec, Laure; Carmona, Loreto; Wit, Maarten de; van Eijk-Hustings, Yvonne; Bertheussen, Heidi; Alison, Kent; Toft, Mette; Kouloumas, Marios; Ferreira, Ricardo J O; Oliver, Susan; Rubbert-Roth, Andrea; et al.
Abstract : In chronic inflammatory rheumatic diseases, comorbidities such as cardiovascular diseases and infections are suboptimally prevented, screened for and managed. The objective of this European League Against Rheumatism (EULAR) initiative was to propose points to consider to collect comorbidities in patients with chronic inflammatory rheumatic diseases. We also aimed to develop a pragmatic reporting form to foster the implementation of the points to consider. In accordance with the EULAR Standardised Operating Procedures, the process comprised (1) a systematic literature review of existing recommendations on reporting, screening for or preventing six selected comorbidities: ischaemic cardiovascular diseases, malignancies, infections, gastrointestinal diseases, osteoporosis and depression and (2) a consensus process involving 21 experts (ie, rheumatologists, patients, health professionals). Recommendations on how to treat the comorbidities were not included in the document as they vary across countries. The literature review retrieved 42 articles, most of which were recommendations for reporting or screening for comorbidities in the general population. The consensus process led to three overarching principles and 15 points to consider, related to the six comorbidities, with three sections: (1) reporting (ie, occurrence of the comorbidity and current treatments); (2) screening for disease (eg, mammography) or for risk factors (eg, smoking) and (3) prevention (eg, vaccination). A reporting form (93 questions) corresponding to a practical application of the points to consider was developed. Using an evidence-based approach followed by expert consensus, this EULAR initiative aims to improve the reporting and prevention of comorbidities in chronic inflammatory rheumatic diseases. Next steps include dissemination and implementation.